If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14-2x=x+8
We move all terms to the left:
14-2x-(x+8)=0
We get rid of parentheses
-2x-x-8+14=0
We add all the numbers together, and all the variables
-3x+6=0
We move all terms containing x to the left, all other terms to the right
-3x=-6
x=-6/-3
x=+2
| a+20=2a | | 0.4(2x-8)=2 | | 14w-11w=15 | | -2x+4=0,5x-21 | | 20=5x-13+6x= | | (12x+7)-9x=4x-8 | | 5=3(r+8)+–1 | | -10x-36=-48 | | z+35=2z-22 | | (2x-1)2-9=0 | | 8k+4k+3k+3k-14k=12 | | 4(3x+8)=-15+11 | | 0,2y-4=20-0,2y | | (40x)–(3x²+7x+54)=0 | | 2w-18=2 | | 3=3(j+18) | | (6x-7)+5x=10x+7 | | 5x+45=540 | | 15u-7u-5u=12 | | 7v-2=v+34 | | c+36=3c+2 | | (10x+7)-5x=6x-7 | | 9z-6z+6z=18 | | 11x-3=-3-12x | | x=5=19 | | 5b-29=b+39 | | 3x-7=-2x-8 | | (7x-17)-3x=x+10 | | 19y+-16y+8y+-10y=17 | | -4n+66=77 | | 5x+3(2x-9=17 | | -5(-2+8r)=330 |